2022
DOI: 10.3389/fcell.2022.818616
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cellular Function by the Urokinase Receptor Signalling: A Mechanistic View

Abstract: Urokinase-type plasminogen activator receptor (uPAR or CD87) is a glycosyl-phosphatidyl-inositol anchored (GPI) membrane protein. The uPAR primary ligand is the serine protease urokinase (uPA), converting plasminogen into plasmin, a broad spectrum protease, active on most extracellular matrix components. Besides uPA, the uPAR binds specifically also to the matrix protein vitronectin and, therefore, is regarded also as an adhesion receptor. Complex formation of the uPAR with diverse transmembrane proteins, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 236 publications
(247 reference statements)
2
28
0
Order By: Relevance
“…Our cell adhesion studies demonstrated that SK-N-BE (2) adhere and form focal adhesions when seeded on laminin, native VN, and PEGylated VN ( Figures 2B,D,E ). These results confirm that PEGylation does not reduce VN biological activity, but more importantly, they demonstrate that neuroblastic cells interact with VN to a similar extent than other studied glycoproteins such as laminin, supporting the role of VN in cell migration ( Alfano, Franco and Stoppelli, 2022 ). However, our results do not provide information about focal adhesion signaling activation, so further experiments such as phosphor-FAK focal adhesion protein assessment could deeper evaluate how cells interact with both PEGylated and native VN.…”
Section: Discussionsupporting
confidence: 76%
“…Our cell adhesion studies demonstrated that SK-N-BE (2) adhere and form focal adhesions when seeded on laminin, native VN, and PEGylated VN ( Figures 2B,D,E ). These results confirm that PEGylation does not reduce VN biological activity, but more importantly, they demonstrate that neuroblastic cells interact with VN to a similar extent than other studied glycoproteins such as laminin, supporting the role of VN in cell migration ( Alfano, Franco and Stoppelli, 2022 ). However, our results do not provide information about focal adhesion signaling activation, so further experiments such as phosphor-FAK focal adhesion protein assessment could deeper evaluate how cells interact with both PEGylated and native VN.…”
Section: Discussionsupporting
confidence: 76%
“…uPAR has been shown to be upregulated in cancer cells, to play a critical role in driving plasminogen-dependent matrix degradation and to affect a variety of physiological and pathological processes, including cell migration, invasion, adhesion, survival and proliferation ( 73 ). In this report, we found a decreased protein abundance but not mRNA of uPAR in MIF-knockdown PDAC cells, suggesting that MIF may not affect PLAUR transcription.…”
Section: Discussionmentioning
confidence: 99%
“…uPAR is a glycosyl-phosphatidyl-inositol anchored (GPI) membrane protein that consists of three domains: D1 (residues 1–92), D2 (residues 93–191) and D3 (residues 192–283) [ 50 ]. uPAR is cleaved between the D1 and D2 domains (linker region) and the GPI-anchor domain by several proteases, such as uPA, plasmin, MMPs, and GPI-specific phospholipase D, and then forms soluble uPAR (suPAR; full length D1-D3, D2D3, and D1) ( Figure 3 ) [ 51 ].…”
Section: The Upa and Upar Systemmentioning
confidence: 99%
“…uPAR is cleaved between the D1 and D2 domains (linker region) and the GPI-anchor domain by several proteases, such as uPA, plasmin, MMPs, and GPI-specific phospholipase D, and then forms soluble uPAR (suPAR; full length D1-D3, D2D3, and D1) ( Figure 3 ) [ 51 ]. uPAR can interact with various transmembrane receptors, including integrins, epidermal growth factor receptor (EGFR), platelet-derived growth factor receptors (PDGFR), vascular endothelial growth factor receptor 2 (VEGFR2), and insulin-like growth factor 1 receptor (IGF1R), as well as regulate signal transduction [ 32 , 50 ]. In addition, uPAR can interact with low-density lipoprotein receptor (LRP), and this uPAR/LRP interaction is associated with uPAR recycling [ 52 ].…”
Section: The Upa and Upar Systemmentioning
confidence: 99%